Promoting healthy aging through intergenerational exchange and digital empowerment: a pilot randomized controlled trial - Cossu, Giulia; Lorrai, Stefano; Galetti, Alessia; Perra, Alessandra; Tusconi, Massimo; Carrà, Giuseppe; Preti, Antonio; Holzinger, Anita; Carta, Mauro Giovanni (Frontiers in Psychiatry, 2025)
BackgroundSocial isolation and loneliness are major public health concern among individuals aged 65 and older, as they are associated with increased risks of morbidity and mortality. Intergenerational programs have emerged as promising interventions to mitigate these issues by fostering social participation and enhancing overall well-being. Interventions that also incorporate digital literacy support may further help address the relevant digital divide, which significantly contributes to social exclusion, particularly among older adults. This pilot study aimed to assess the feasibility and preliminary efficacy of a psychosocial intervention focused on intergenerational exchange and digital literacy.MethodsA 12-week crossover randomized controlled trial (RCT) design was employed. The intervention engaged younger and older participants in co-preparing seminar presentations, discussing these, and participating in plenary meetings—both in-person and online—on self-selected health, cultural, and topics meaningful from an individual perspective. Feasibility indicators included dropout rates and participant satisfaction. Preliminary measures of improvement were assessed using the Short Form Health Survey (SF-12) for quality of life, the Brief Social Rhythms Scale (BSRS) for the regularity of social and biological rhythms, and the Patient Health Questionnaire-9 (PHQ-9) for depressive symptoms.ResultsA total of 12 participants were included in the experimental group and 9 in the control group. Feasibility outcomes showed an overall dropout rate of 28.57%, similarly to comparable trials. Notably, the attrition rate was lower in the experimental group (16.67%). Participant satisfaction was particularly high (M = 37.06, SD = 3.08). Preliminary analyses revealed a statistically significant improvement only in BSRS; 66.6% vs. 26.67%, p = 0.033. Trends toward improvement were observed in PHQ-9 and SF-12, although these did not reach statistical significance.ConclusionsThe findings suggest very high satisfaction and moderate engagement among older adults involved in the program. Given the positive impact on the regularity of biological and behavioral rhythms—recognized as key protective factors in healthy aging—the improvement observed is particularly promising. Future studies with larger samples and extended follow-up periods are needed to corroborate this preliminary evidence.Clinical trial registrationClinicalTrials.gov, identifier NCT06162871.